FORMULATION AND EVALUATION OF KETOCONAZOLE NIOSOMAL GEL - Kaur, Paninder; Dua, J.S; Prasad, D.N (Asian Journal of Pharmaceutical Research and Development, 2018)
ABSTRACT In recent years, treatment of infectious disease through Novel Drug delivery system (NDDS) has undergone a revolutionary shift. Niosomes are a Novel Drug Delivery system which has potential application to treat infectious disease topically. Niosomes are non-ionic surfactant vesicles, in which medication is encapsulated in a vesicle for controlled drug release. Ketoconazole niosomes were prepared by using Cholesterol, Span 60/ Span 40 as surfactants, chloroform, and diethyl ether using rotary vacuum evaporator method. Formulation was then evaluated for particle size, drug content, entrapment efficiency, and in-vitro drug release studies. The Entrapment efficiency and drug content were calculated at 225nm using UV spectrophotometer. The drug content was found to be 70.37% for Span 40 and 72.81% for Span 60.The percentage of drug entrapment in niosomes was 60.3 % for Span 40 and 62.21 % for Span 60. FT-IR studies for niosomes containing Span 40 shows -CH stretching (Aliphatic) at 2891 cm-1and2925 cm-1 for niosomes containing Span 60. Ketoconazole niosomal gel was prepared using Carbopol 940, glycerol, Triethanolamine and distilled water. Evaluation of niosomal gel was determined by Physical appearance, pH, viscosity, drug content, entrapment efficiency and In-vitro diffusion studies.The percentage of the drug release from the niosomal gel was found to be 40.78 % for Span 40 and 33.75% for Span 60 . This delivery system is cost effective and simple to prepare as only the prepared gel of niosomes was introduced in Rotary vacuum evaporator for solvent evaporation.